LEADERSHIP, WORK DISCIPLINE, AND WORK ENVIRONMENT EFFECTS ON ASN PERFORMANCE: THE MEDIATING ROLE OF JOB SATISFACTION AT THE MALANG REGENCY DPRD SECRETARIAT - Permatasari, Indriani Detty; Suja’i , Ahmad Yusuf Imam; Sunaryo , Hadi (International Journal of Cultural and Social Science, 2025)
This study analyzes the effects of leadership, work discipline, and work environment on the performance of State Civil Apparatus (ASN) employees at the Malang Regency DPRD Secretariat, with job satisfaction as an intervening variable. A quantitative explanatory approach was employed using census data from 73 ASN employees collected through questionnaires. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The measurement model shows satisfactory convergent validity and construct reliability. The structural model indicates that leadership and work environment significantly affect job satisfaction, while work discipline does not. Moreover, work discipline significantly influences employee performance, whereas leadership, work environment, and job satisfaction have no significant effect. Job satisfaction does not mediate the relationship between the independent variables and employee performance. These findings suggest that other factors may play a more dominant role in influencing ASN performance and provide insights for improving human resource management effectiveness.